Filsafat Esensialisme Sebagai Pendukung Ideologi Pendidikan Seni Di Indonesia - Richard Kapoyos; Laura Megawaty Manalu (Clef: Jurnal Musik dan Pendidikan Musik, 2022)
Idealism and Realism are philosophical schools that make up the style of Essentialism. The contribution given by each of these is eclectic, meaning that these two schools of philosophy meet as supporters of Essentialism. Education in Indonesia is getting tougher because of the rapid onslaught of foreign cultures and increasingly rapid technological advances. Education in Indonesia seems to have lost its identity due to adopting too many foreign cultures. Traditions and local wisdom that should be the hallmark of the Indonesian people are sinking and being replaced by foreign cultural products. Even though many have expressed their thoughts about thinking globally acting locally, the identity crisis still continues to plague our nation. In these conditions, education should position itself as an inseparable part of a civilization.